Pendidikan Kesehatan, Pemeriksaan dan Deteksi Dini Pencegahan Penyakit Tidak Menular melalui Kegiatan Olah Raga Fisik di Wilayah Kerja Puskesmas Tamalanrea Makassar - Hilal, Achmad; Rachman, Arif; Hardianti, Hardianti; Sari, Lely Meriaya; Imrawati, Imrawati; Utami, Yuri Pratiwi (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Non-communicable diseases are a group of diseases that cannot be transmitted, but non-communicable diseases are the main cause of death in 68% of the world. In fact, currently the incidence of non-communicable diseases has reached ±38 million sufferers and is predicted to continue to increase to reach 52 million people in 2030. This activity aims to increase people's knowledge and healthy living behavior regarding non-communicable diseases, empower health cadres and community health centers to carry out early detection of non-communicable diseases through anthropometric measurements, and reduce the prevalence and complications of non-communicable diseases in the community. The benefits of this activity are providing accurate and easy to understand information about non-communicable diseases through leaflets, improving people's health and quality of life, and supporting government programs in preventing and controlling non-communicable diseases. The methods used in this activity are health checks, nutritional counseling and community service demonstrations through training and counseling activities with Health Education, Examination and Early Detection, Prevention of Non-Communicable Diseases through Physical Sports Activities in the Tamalanrea Makassar Health Center Working Area. The results of the education were assessed by completing a pre-post education questionnaire and a significant increase in scores was obtained, meaning that the education carried out had increased the knowledge of women of childbearing age and the elderly regarding non-communicable diseases and their prevention.